Proposed Systems for Knowledge Sharing Between the Faculty Concentrating in the Middle East and Gulf Region Area - Ashraf Badawood, Dr; Hamad AlBadri, Dr (International Journal of Engineering and Technology, 2018)
Knowledge sharing is an imperative aspect of every higher education institution. Among the different parties that require information to be shared among them are faculties because knowledge gained in different faculties are also applicable to others. The motivation for understanding the knowledge sharing behavior in faculties in the Middle East and Gulf Region area is because of the current weaknesses in the current knowledge sharing systems and thus, solutions for these weaknesses are recommended. The aim of this study is to provide an understanding of knowledge sharing behavior in the middle-east region and particular in the gulf region. The level of usage of knowledge sharing systems in the university institutions is the main focus while also determining the factors influencing the same. The advantages and disadvantages associated with knowledge sharing are discussed. Effects of knowledge sharing on studentsâ€™ performance were also assessed. Qualitative research design was used to gather data for this study where secondary sources were used. These included books, scholarly journal articles, reports and credible sources from the internet. From the findings of the research, it was established that factors that some of the main factors that affect the knowledge sharing in universities in the Middle East include inadequate capital, technology resources and cultural differences in the region. Several recommendations have been made to enhance knowledge sharing and these include more commitment by the government to support it by allowing more collaboration between the local universities and foreign academicians who are well experienced in terms of information sharing.Â Â